FRI0341 Influence of Tapering Etanercept on Work Productivity Outcomes in Patients with Early Rheumatoid Arthritis Tapered: 117 Week Results from the Prize Study. (9th June 2015) - Zhang, W.; Bansback, N.; Sun, H.; Pedersen, R.; Kotak, S.; Anis, A.H.
Abstract : Background: Previous results have demonstrated that etanercept 50mg (ETN50) plus methotrexate (MTX) can reduce work loss in patients with early rheumatoid arthritis (RA). Objectives: To assess the impact on work productivity of reducing and withdrawing etanercept in patients who had reached remission. Methods: Phase I of the PRIZE trial recruited patients with early, moderate-to-severe RA to an open-label ETN50+MTX for 52 weeks. Phase II was a 39-week, randomized, and double-blind comparison of dose reduction to ETN25+MTX, MTX or Placebo in subjects who had achieved response during Phase I. Phase III was a 26-week observational phase in which Phase II responders progressively stopped treatment. The Valuation of Lost Productivity (VOLP), a validated instrument developed to estimate productivity impacts from a societal perspective, was completed approximately every 13 weeks. One of the main VOLP outcomes, the 3-month paid work productivity loss, was calculated as the sum of lost work hours attributable to absenteeism, presenteeism (reduced productivity while at work) and employment status changes. Patients included in the Phase II analysis were employed at week 52 with ≥1 follow-up during Phase II. Those included in Phase I and III were the Phase II study patients who were also employed at baseline with ≥1 follow-up during Phase I and who were also employed at week 91 with ≥1 follow-up during Phase III, respectively. Results: A total of 116, 120 and 55 subjects were included in our Phases I, II and III analyses, respectively. At week 52, the 3-month paid work productivity loss was 21.8 hours, 12.8 hours and 14.0 hours, respectively. The productivity loss increased at week 64 from week 52 and dropped at week 76 for all treatment groups. Nonetheless, the productivity loss continued rising after week 76 for the Placebo group (71.9 hours at week 91) but not for the other two groups (21.9 hours for ETX25+MTX and 27.6 hours for MTX). However, the loss differences between groups were not statistical significant. In contrast, for patients who were also employed at baseline, the 3-month paid work productivity loss dropped sharply from 93.1 hours at baseline to 14.0 hours at week 39 and then flattened at week 52 (15.8 hours) during Phase I. All patients who remained in the study, regardless of the treatment group, maintained their paid work productivity loss during Phase III the same as their loss at the end of Phase II. In addition, the changing trend of the employment rate was similar for the ETN25+MTX and MTX groups. The employment rate dropped more sharply during Phases II and III for the Placebo group than the other two treatment groups. Conclusions: The work productivity gain in Phase I as a result of ETN50+MTX was marginally lost in the dose reduction treatment groups, ETN25+MTX and MTX, but substantially lost in the Placebo group during Phase II of the trial. Patients who still remained in the study maintained their paid work productivity during Phase III. The patients in the ETN25+MTX and MTX groups were more able to maintain their employment than those in the Placebo group. Disclosure of Interest: W. Zhang: None declared, N. Bansback: None declared, H. Sun: None declared, R. Pedersen Employee of: Pfizer Inc., S. Kotak Employee of: Pfizer Inc., A. Anis Grant/research support from: Pfizer Inc.